2021
DOI: 10.3389/fneur.2021.632307
|View full text |Cite
|
Sign up to set email alerts
|

Review of Multi-Modal Imaging in Urea Cycle Disorders: The Old, the New, the Borrowed, and the Blue

Abstract: The urea cycle disorders (UCD) are rare genetic disorder due to a deficiency of one of six enzymes or two transport proteins that act to remove waste nitrogen in form of ammonia from the body. In this review, we focus on neuroimaging studies in OTCD and Arginase deficiency, two of the UCD we have extensively studied. Ornithine transcarbamylase deficiency (OTCD) is the most common of these, and X-linked. Hyperammonemia (HA) in OTCD is due to deficient protein handling. Cognitive impairments and neurobehavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Ammonia toxicity in the brain is tightly connected to glutamine metabolism [21][22][23]. This observation is supported by MRS that has shown high glutamine concentrations during HA in rat models [24,25] but also in human with UCD or hepatic encephalopathy (Table 1) [13,14,[26][27][28][29][30][31][32][33][34][35][36][37]. Reduction in myoinositol and choline [34] Valproateinduced encephalopathy Metabolic-toxic lesion pattern with bilateral T2-hyperintense lesion in the cerebellar white matter and in the globus pallidus Elevated glutamine and glutamate.…”
Section: Discussionmentioning
confidence: 93%
“…Ammonia toxicity in the brain is tightly connected to glutamine metabolism [21][22][23]. This observation is supported by MRS that has shown high glutamine concentrations during HA in rat models [24,25] but also in human with UCD or hepatic encephalopathy (Table 1) [13,14,[26][27][28][29][30][31][32][33][34][35][36][37]. Reduction in myoinositol and choline [34] Valproateinduced encephalopathy Metabolic-toxic lesion pattern with bilateral T2-hyperintense lesion in the cerebellar white matter and in the globus pallidus Elevated glutamine and glutamate.…”
Section: Discussionmentioning
confidence: 93%
“…Multimodal neuroimaging in OTCD has shown value in identifying brain biomarkers of disease in female heterozygotes that correlated with measures of cognitive dysfunction in the domains of executive dysfunction. Neuroimaging studies have shown that the white matter tractography in frontal lobe is impacted by severe or mild HA, thereby providing a hypothesis for executive dysfunction in OTCD with partial enzyme activity (Sen et al, 2021(Sen et al, , 2022. Studies using DTI have shown that individuals with OTCD have reduced white matter integrity in specific regions of the brain, which may be related to the cognitive and behavioral problems observed in these individuals (Gropman et al, 2010).…”
Section: Neurocognitive Findings In Females With Otcdmentioning
confidence: 99%
“…The urea cycle disorders (UCD) are a group of genetic disorders associated with an enzyme or a carrier protein insufficiency [ 20 , 21 ]. Table 1 shows the specific UCD and prevalence.…”
Section: Rare Diseasesmentioning
confidence: 99%
“…As referenced above, neurological impairment is of primary significance to the UCD [ 13 , 26 ]. For decades, EEG and MRI have been the main modalities for studying neurological dysfunction in the UCD [ 20 ]. fNIRS has emerged as a non-invasive technique and could serve as a surrogate to fMRI with better portability in assessing hemodynamic change in the brain and further assist the development of new imaging biomarkers [ 31 ].…”
Section: Rare Diseasesmentioning
confidence: 99%
See 1 more Smart Citation